Fosfatos de cálcio modificados com nióbio e seus compósitos com niobatos lamelares aplicados como agentes antimicrobianos e adsorventes - Araújo, Rafael de Carvalho (2022)
Calcium phosphates including hydroxyapatite, Ca10(PO4)6(OH)2, fluorapatite Ca10(PO4)6F2 and tricalcium beta-phosphate, β-Ca3(PO4)2, are among the most widely used bioceramics for biotechnological applications. However, all these phosphates have application limitations such as low adsorptive capacity against some drugs, low antimicrobial activity and lower mechanical resistance to some segments of bone tissue. An alternative to improve the properties of the phosphates has been the doping with different ions and the formation of composites with metallic and non-metallic oxides. In this sense, in present thesis niobium-modified calcium phosphates and composites between hydroxyapatite and tricalcium beta-phosphate with potassium triniobate and potassium hexaniobate were obtained. The solids obtained from the niobium doped Ca10(PO4)6F2 with were applied as adsorbents for tetracycline and the antibacterial activities against S. aureus of the doped solids or loaded tetracycline Ca10(PO4)6F2 were evaluated. Calcium phosphates were modified by the structural insertion of niobium, using niobium pentachloride (NbCl5) and ammonium niobium oxalate (NH4H2[NbO(C2O4)3]) as precursors via a co-precipitation reaction where the mol amounts of dopants were varied in 1% to 10%. For the synthesis of the composites, two colloidal solutions derived from the exfoliation of layered potassium niobates were used for the in situ incorporation of the phosphate precursors or deposition of the obtained phosphates. The materials obtained were characterized by X-ray diffraction (XRD) with Rietveld refinement, infrared absorption spectroscopy (FTIR), X-ray fluorescence (XRF), Raman spectroscopy, X-ray excited photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) coupled to EDS. Refinement Rietveld suggested that niobium replaced calcium at site (II) of hydroxyapatite, in addition to causing changes in lattice parameters a and c, and volume. XRF analysis indicaded that the presence of niobium in the modified calcium phosphates in mol proportions close conditions used in the synthesis. XPS spectra suggested the presence of Nb5+ in all modified phosphates. It was observed that the insertion of Nb5+ in the structure of Ca10(PO4)6F2 decreased the tetracycline adsorption. Antimicrobial activity against S. aureus improved after phosphate modification compared pristine matrices, especially for the tetracycline loaded Ca10(PO4)6F2, which antimicrobial activity was 100%. For the composites, the typical diffraction profile for each of the phosphates used was observed and also the niobates. All results indicated that Nb-doped calcium phosphates were successfully prepared and that the composites between hydroxyapatite and beta tricalcium phosphate with layered niobates showed both phases, especially for the in situ route.